Biomorphometric analysis of ilio‐sacro‐iliacal corridors for an intra‐osseous implant to fix posterior pelvic ring fractures. Issue 2 (18th November 2014) - Gras, Florian; Hillmann, Sophia; Rausch, Sascha; Klos, Kajetan; Hofmann, Gunther O.; Marintschev, Ivan
ABSTRACT It is hypothesized that ilio‐sacro‐iliacal corridors for a new envisioned pelvic ring implant (trans‐sacral nail with two iliacal bolts = ISI‐nail: ilio‐sacro‐iliacal nail) exists on the level of S1‐ or S2‐vertebra in each patient. The corridors of 84 healthy human pelves (42x ♂; 42x ♀, 18–85 years) were measured in high resolution CT scans using the Merlin Diagnostic Workcenter Software. Trans‐sacral corridors (≥9 mm diameter) on the level of S1 and S2 were found in 62% and 54% of pelves with a mean length [mm ± SD] of 164 ± 12.9 and 142 ± 10.2. Corresponding iliac corridors were present in all specimens in caudally tilted axial planes of 37.8 ± 0.67° and 53.7 ± 0.94° in relation to the operating table plane and divergent angulations of 69.0 ± 0.49° and 70.1 ± 0.32° in relation to the sagittal midline plane. Sacral dysmorphism, with compensatory larger S2 corridors were prevalent in 24% of pelves; ilio‐sacro‐iliacal osseous corridors for the envisioned implant were found in 88% of pelves on the level of S1 or S2. In the remaining 12% with too narrow corridors for any trans‐sacral implant (screws, bars, ISI nail) alternative fixation methods have to be considered. Expected advantages of the envisioned ISI nail compared to available fixation devices are discussed. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:254–260, 2015.